STABILITAS FISIK DAN MUTU HEDONIK SIRUP DARI BAHAN TEMULAWAK (Curcuma xanthorrhiza Roxb.) - Nutrisia Aquariushinta Sayuti; Agus Winarso (Universitas Wahid Hasyim Semarang, 2014)
ABSTRACT Curcuma xanthorrhiza that contain of curcumin and essential oil make the taste isn’t delicious. Syrup form can cover the lack of the flavor. The study aimed to describe the results of the physical stability test and hedonic test of Curcuma syrup. It was an experimental research by analyzing the physical stability and hedonic quality of Curcuma syrup. Physical stability test was done by storing the syrup at a temperature of 400C for 8 weeks, analyzing the organoleptic, viscosity and acidity (pH) every 2 weeks. 55 of 4th semester students, Jamu Department, Polytechnic of Surakarta, 2014/2015 act as a semi-trained panelists in a hedonic test. The results concluded that the viscosity of syrup which was originally ± 190 mP.as decreased in storage for 2 weeks to ± 170 mP.as and finally stabilized to week 8th. The acidity degree stable at pH 4. The organoleptics were no change, it was brownish yellow, a distinctive smell of curcuma, citrus flavor and texture rather thick. The panelists’ assessment against the syrup was 70.91% of panelists liked the scent, 78.18% of panelists liked the taste, 85.46% of panelists liked the texture and 83.64% panelists liked the color of syrup. Keywords: Curcuma, Syrup, physical stability, hedonic